Modulation of insulin gene expression with crispr/cas9-based transcription factors - Alzhanuly, B.; Mukhatayev, Z. Y.; Botbayev, D. M.; Ashirbekov, Y.; Katkenov, N. D.; Dzhaynakbaev, N. T.; Sharipov, K. O. (Macedonian Journal of Medical Sciences. - 2021., 2021)
The discovery and use of CRISPR/Cas9 technology have enabled researchers throughout the globe to continuously edit genomes for the benefit of science and medicine. Diabetes type I is one field of medicine where CRISPR/Cas9 has a strong potential for cell therapy development. The long-lasting paucity of healthy cells for clinical transplantation into diabetic patients has led to the search of new methods for producing β-cells from other human cell types. Embryonic stem cells are being studied worldwide as one most promising solution of this need. AIM: The aim of the study is to check the feasibility of modulating human insulin transcription using CRISPR/Cas9-based synthetic transcription regulation factors. METHODS: A new approach for creating potential therapeutic donor cells with enhanced and suppressed insulin production based on one of the latest achievements of human genome editing was developed. RESULTS: Both synthetic transcription activator (VP64) and transcription repressor (KRAB) proteins were shown to function adequately well as a part of the whole CRISPR/Cas9-based system. CONCLUSION: We claim that our results have a lot to offer and can bring light to many studies where numerous laboratories are struggling on to treat this disease. Целью исследования является проверка возможности модуляции транскрипции человеческого инсулина с помощью синтетических факторов регуляции транскрипции на основе CRISPR / Cas9. МЕТОДЫ. Был разработан новый подход к созданию потенциальных терапевтических донорских клеток с повышенной и подавленной выработкой инсулина, основанный на одном из последних достижений редактирования генома человека. РЕЗУЛЬТАТЫ: Было показано, что белки синтетического активатора транскрипции (VP64) и репрессора транскрипции (KRAB) адекватно хорошо функционируют как часть всей системы на основе CRISPR / Cas9. ЗАКЛЮЧЕНИЕ: Мы утверждаем, что наши результаты могут многое предложить и могут пролить свет на многие исследования, в которых многочисленные лаборатории пытаются лечить это заболевание.
Keywords: импакт-фактор 2021; дальнее зарубежье; научный журнал; периодическое издание; медицина; сахарный диабет; инсулин; лечение заболевания; скопус